Prewriting Activities in Teaching EFL Writing - Suharti, Dwi Sloria; Permanasari, Nurbaiti Eka; Khuluqo, Ihsana El (UICELL, 2018)
In this paper, the researchers would like to propose a teaching EFL writing course: News Story, which the researchers have used in an EFL classroom context. This effort is different from others in some occasions. Firstly, in the stages of developing ideas of a news story: a biography news, the researchers encourage students to seek for related information for their composition through pre writing activities such as, the activity of research that is by interviewing: preparing some questions and asking those questions to the (intended person) source. Secondly, at the phase of drafting, the researchers ask students to work cooperatively, to construct the main ideas and supporting ideas this activity ends with the results which are sentences then paragraphs. Furthermore, before the researchers provide a writing task: writing a biography news, students are given transitional words to make their composition coherently. Lastly, they upload their composition in their blog. In short, in the proposed teaching EFL writing: a biography news story, by interviewing, students can understand how to organize the writing material according to the necessities of the writing task; writing biography News. To sum up, prewriting activities; through interviewing can assist EFL students to generate the ideas which can inspire and aid them realize both what they want to write and how to write it on their writing task: A Biography News.